The impact of implicit social conflict on ecosystem conservation in protected areas: a case study of Patatso National Park - Yuxi Zeng; Ling-en Wang; Linsheng Zhong (Ecology and Society)
Ecosystem conservation in protected areas (PAs) depends on friendly behavior (e.g., no illegal wildlife hunting) toward the ecosystem by residents living within a PA, which can be prompted by good cooperation with PA managers. However, conflicts often arise between local residents and PA managers (e.g., disproportionate allocation of benefits), existing in the form of implicit conflicts (e.g., non-compliance with policy implementation) that can affect conservation goals of a PA. Here, we develop a theoretical framework, synthesizing theories related to conflict, displaced aggression, routine activity, withdrawal behavior, and livelihood, to explain how implicit conflicts affect ecological misbehavior of residents living within PAs. We collected data from 155 residents living in Patatso National Park, China, during April–June 2022 to test the relationships between our framework variables (i.e., implicit conflicts, ecological misbehavior, withdrawal intention, livelihood strategies) using partial least squares-structural equation modeling. Results show that: (1) higher levels of implicit conflicts strengthen residents’ withdrawal intention from environmental responsibility and increase ecological misbehavior; (2) the effect of implicit conflicts on withdrawal intention and ecological misbehavior is moderated by the livelihood strategies of residents; (3) for residents adopting inner livelihood strategies (e.g., herding), higher implicit conflicts lead to stronger withdrawal intention and ecological misbehavior; for those adopting outer livelihood strategies (e.g., working in cities or industries), implicit conflicts have no significant effect on withdrawal intention or ecological misbehavior. This research elucidates the mechanisms by which social conflict influences residents’ ecological misbehavior by clarifying the mediating role of withdrawal intention and the moderating effects of livelihood strategies, offering practical insights for managers to enhance the effectiveness of ecosystem conservation.